OC-027 Fgf19 Levels In Subjects With Primary Bile Acid Diarrhoea And Elevated Triglycerides. (9th June 2014) - Nolan, J; Pattni, S; Walters, JR; Johnston, IM
Abstract : Introduction: There is evidence that primary bile acid diarrhoea (PBAD) is caused by disordered bile acid homeostasis. Most patients with severe PBAD have low fasting serum FGF19 which fails to rise above 300 pg/ml postprandially. Different patterns of postprandial FGF19 response have been demonstrated, with some resembling those of healthy individuals. Others have shown that serum triglyceride levels reflect expression of the luminal bile acid transporter ASBT. It is hypothesised that a subset of individuals with hypertriglyceridaemia have different fasting FGF19 levels and postprandial FGF19 response. Methods: Study 1: 162 patients with chronic diarrhoea were recruited prospectively. All patients underwent routine testing to exclude other causes of diarrhoea and had SeHCAT tests. Patients were classified as having PBAD, or unexplained chronic diarrhoea (CD). Other diagnoses were excluded. Fasting blood samples were taken and processed for triglycerides and FGF19. Subjects with either diagnosis were also analysed within 2 subgroups according to triglyceride level (cut off 2.30 mmol/l). Study 2: 18 subjects took part in a study to examine FGF19 levels over the course of 6 h. After an overnight fast, blood was sampled every 90 min for 6 h. Meals were provided at 9 am and 12 noon. Serum FGF19 was quantified by ELISA using a commercially available kit. Triglycerides were quantified by standard colorimetric technique. Mann-Whitney and Spearman rank correlation tests were used in analyses. Results: Study 1: Overall subjects with elevated triglycerides (n = 18) have significantly lower SeHCAT retention (median 7.95 vs. 19.5% p = 0.01). Subjects with severe BAD with elevated triglycerides had higher fasting FGF19 levels (241 vs 101 pg/l p = 0.02). Study 2: There was no significant difference in fasting triglycerides between different phenotypes of FGF19 response (previously presented work). The percentage increase in FGF19 from fasting to 90 min after breakfast correlates with fasting serum triglyceride level (R = 0.59, p < 0.005). Conclusion: We have identified a subset of PBAD subjects with high triglycerides and fasting FGF19 levels comparable to healthy individuals. The post prandial rise in FGF19 suggests no defect in the response of FGF19 synthesis in this subset. It may instead be caused by impaired BA absorption due to reduced ASBT expression which is also manifested as high serum triglycerides. PBAD may be a heterogenous condition with more than one underlying key abnormality. Disclosure of Interest: None Declared.